Corpo e escrita: imaginários literários (Revista da UFMG, 2012)
This work analyzes, with a comparative focus, the representations of the feminine body in literary texts by women in which this body appears as an effective locus of resistance and transgression. In this sense, this body can be conceived as a discursive entity and a cultural metaphor, marked by gender, ethnic, sexuality and  lass issues. The works by women authors analyzed here rewrite the traditional and idealized version of a political body and reveal the power of the feminine body as a politically inscribed entity and, therefore, as a space of individual determination and subversion.